DIGITALISASI DALAM KEGIATAN KATEKESE SEBUAH STUDI LITERATURE REVIEW - Muda, Stefanus; Muda, Florianus Pruda (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
This study aims to analyse and synthesise existing literature on the advantages and disadvantages of digitisation in catechesis. Data was collected from relevant journal articles published in the last five years. The results of the study show that although digitisation in catechetical activities offers many advantages, it also has very urgent disadvantages, such as the lack of knowledge among the faithful in utilising and operating digital media for catechetical activities, the lack of supporting infrastructure, the lack of interest among the faithful in spiritual content, some of the faithful utilising digital media to convey information about certain meetings, and some of the faithful also passively participating in online catechesis. Therefore, this study provides recommendations to the Church, catechists, and the faithful to overcome these challenges in order to increase the effectiveness of digitisation in catechesis.